Pengelolaan Koperasi Pesantren untuk Kesejahteraan Ekonomi Masyarakat: Telaah Surah al-Hasyr Ayat 7 - Ahmad Lutfi Rijalul Fikri; Muaidy Yasin; Akhmad Jupri (Universitas Darussalam Gontor, 2018)
Al-Qur’an with its verses becomes the economic foundation that has given the principles of life in relationships between man and his fellowmen. It contains rules and guidance to do good things and tyranny. Al-Qur’an which is foundation of the whole teachings of Islam is not just about rules and prohibitions, but provides assurance for the realization of economic prosperity of the community. The writer intends to reveal the clarity of the concept of pesantren cooperative management for the economic welfare of community in the perspective of surah al-Hashr verse 7. Al-Qur’an believes that economic welfare is not only the problem of economic distribution materially but also concerning non material and other felds. Therefore, to achieve growth and development materially and spiritually, Islamic economics has characteristics in its growth, which is all-round, balanced, realistic, fair, responsible, suffcient, and focusing on human beings in accordance with their right as khalifah. These characteristics indicate that the goal of growth and economic development in Islam is the opportunity of all members of any community of race, religion, and character to gain prosperity, so that everyone can experience the blessings and grace of Allah. Al-Qur’an demands all to carry out the whole teaching of Islam in all aspects of their life. Therefore, economic welfare should be viewed as the embodiment of God’s command to his servants. Then, economic welfare would be a continuous effort of mankind to do the best, both to God and fellow human beings based on the guidance of al-Qur’an.